Frontal Sinus Mucosa Bacteriological Features: Evaluation after Unintentional Opening in Neurosurgery - Sato, Hiroki; Ooigawa, Hidetoshi; Suzuki, Kaima; Yanagawa, Taro; Lepic, Milan; Otsuka, Munehiro; Fushihara, Goji; Kurita, Hiroki (Journal of Neurological Surgery Part B: Skull Base, 2023)
Objectives The bacteriological features of the frontal sinus mucosa may impose significant complications in neurosurgery, when breached unintentionally. This study aimed to investigate the bacterial flora in patients undergoing frontal craniotomy for cerebrovascular substrate surgery.Design This is a single-center prospective study.Setting When mucosal laceration occurred, the patients underwent frontal sinus reconstruction with mucosa reconstruction, preserving the nasofrontal duct.Participants We enrolled eight consecutive patients who underwent bifrontal craniotomy associated with frontal sinus mucosa laceration.Main Outcome Measures A portion of the mucosa was extracted during the reconstructive procedure and was sent for microbiological analysis.Results None of the patients presented with the bacterial flora in the mucosal cultures. No patient experienced postoperative cerebrospinal fluid leakage or meningitis. One patient with a clinical history of chronic maxillary sinusitis presented with a subcutaneous abscess around the forehead at 9 months postoperatively. The patient rapidly recovered after receiving oral administration of antibiotics.Conclusions Our findings demonstrated that the frontal sinuses were maintained in an aseptic environment in all cases. The results may encourage the development and wider use of transfrontal sinus approaches.
Keywords: frontal sinus; injury; bifrontal approach; craniotomy; complication